FAKTOR PENYEBAB KELUARGA MAMPU MENERIMA BANTUAN PROGRAM KELUARGA HARAPAN (PKH) DI NAGARI ALAHAN NAN TIGOKECAMATAN ASAM JUJUHAN KABUPATEN DHARMASRAYA - Parida, Parida; Yuhelna, Yuhelna; Erningsih, Erningsih (Universitas Tanjungpura, 2022)
PKH assistance is one form of assistance aimed at underprivileged communities to be able to help improve their lives, but a lot of this assistance that is obtained is not in accordance with its target. Where people who can afford it also get help. This is of course not in accordance with the applicable provisions relating to the terms of the beneficiary. The purpose of this study was to analyze the factors that cause families to be able to receive the Family Hope Program (PKH) assistance from Nagari Alahan Nan Tigo, Asam Jujuhan District, Dharmasraya Regency. The theory used in this study is the theory of functional structure proposed by Robert K. Merton. The research was conducted in Nagari Alahan Nan Tigo, Asam Jujuhan District, Dharmasraya Regency. This study used qualitative research methods with descriptive research type. Withdrawal of informants is done by purposive sampling technique, with the informants are well-off families who receive assistance. The data collection method in this study begins with observation, interviews, and document studies. Data analysis was carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that there were several factors that caused capable families to also receive PKH assistance (Program Keluarga Harapan) in Nagari Alahan Nan Tigo, Asam Jujuhan District, Dharmasraya Regency, including 1) Relationship between PKH recipients and data collection officers 2) lack of understanding of PKH recipients on the use of aid.